Efficient Motion Detection Algorithm in Video Sequences (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Human  motion  analysis  concerns  the detection,  tracking  and  recognition  of  people  behaviors,  from image  sequences  involving  humans. A  reference  frame  is  initially  used  and  considered  as  background  information. While a new object enters into the frame, the foreground information and background information are identified using the reference frame as background model.In this paper, an efficient algorithm is proposed for objects detection in real time video sequences. The method aims at tracking an object like (human) in motion using background subtraction technique. The tracked objects are subject to different pre and post image processing in order to extract the most important features (frame preprocessing is used for shadow removal using morphological operations). They can be used later for recognition in different security system such as (human detection for surveillance). Experimental results show that the proposed method is very efficient in terms of reliability and accuracy of detection.